2017
DOI: 10.18632/oncotarget.17757
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA NEAT1 enhances epithelial-to-mesenchymal transition and chemoresistance via the miR-34a/c-Met axis in renal cell carcinoma

Abstract: Long non-coding RNAs (lncRNAs) have emerged as new gene regulators and prognostic markers in various cancers. Although the lncRNA nuclear enriched abundant transcript 1 (NEAT1) has been associated with tumorigenesis, its functions in renal cell carcinoma (RCC) have not been elucidated. We determined that NEAT1 is up-regulated in RCC tissue compared to corresponding non-tumor tissue. High NEAT1 expression was associated with tumor progression and poor survival in RCC patients. NEAT1 knockdown suppressed RCC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…12 Also, NEAT1 knockdown repressed the cell proliferation, migration and invasion by reversing the epithelial-to-mesenchymal transition phenotype, and increased the sensitivity of renal cell carcinoma to sorafenib in vitro. 13 In addition, NEAT1 was upregulated in NPC and reduction of NEAT1 reversed epithelial to mesenchymal transition phenotype and sensitized NPC cells to radiation by modulating miR-204/ZEB1 axis. 14 However, the function of NEAT1 and its underlying mechanisms in NPC chemoresistance remain poorly understood.…”
Section: Introductionmentioning
confidence: 96%
“…12 Also, NEAT1 knockdown repressed the cell proliferation, migration and invasion by reversing the epithelial-to-mesenchymal transition phenotype, and increased the sensitivity of renal cell carcinoma to sorafenib in vitro. 13 In addition, NEAT1 was upregulated in NPC and reduction of NEAT1 reversed epithelial to mesenchymal transition phenotype and sensitized NPC cells to radiation by modulating miR-204/ZEB1 axis. 14 However, the function of NEAT1 and its underlying mechanisms in NPC chemoresistance remain poorly understood.…”
Section: Introductionmentioning
confidence: 96%
“…The lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) plays critical oncogenic roles and facilitates tumorigenesis of various human cancers and high NEAT1 expression is associated with a poor prognosis in cancer patients . Aberrant overexpression of the lncRNA NEAT1 has been documented in different types of solid tumors, such as renal cell carcinoma, ovarian cancer, non‐small cell lung cancer (NSCLC), breast cancer, in which its high levels are associated with poor prognosis . However, its role in MM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NEAT1 was elevated in multiple cancers, and it acted as an oncogene in these cancers (F. Liu et al, 2017;Y. Liu et al, 2018;Yu et al, 2017).…”
mentioning
confidence: 99%